Case report: Prenatal diagnosis of Ectrodactyly–Ectodermal dysplasia–Cleft syndrome (EEC) in a fetus with cleft lip and polycystic kidney - Biwei, He; Min, Su; Yanlin, Wang; Xinrong, Zhao; Li, Gao; Renyi, Hua; Jinling, Sun; Shan, Wang; Yi, Wu; Weiwei, Cheng (Frontiers in Genetics, 2022)
Ectrodactyly-Ectodermal Dysplasia-Cleft (EEC) syndrome is an autosomal dominant disorder characterized by ectrodactyly, ectodermal dysplasia, and orofacial clefting. Reduced penetrance is manifested in these core features and additional under-recognized features, especially in prenatal cases. Here we present a fetus with EEC syndrome at 22 weeks gestation, in which cleft lip and palate, and right polycystic kidney are shown by prenatal ultrasound. A de novo missense mutation of R304W in the TP63 gene is confirmed by whole exome sequencing associated with the EEC syndrome. We further investigate the reported TP63-related prenatal cases and provide a more complete picture of the prenatal phenotypic spectrum about EEC. It illustrates the potential severity of genitourinary anomalies in TP63-related disorders and highlights the need to counsel for the possibility of EEC syndrome given the occurrence of genitourinary anomalies with orofacial cleft or limb deformities.